Lepidotrigona Smith (Apidae: Meliponinae) in Sibolga, North Sumatra: Morphology, morphometric and nest entrance structure - Wicaksono, Anggun; Atmowidi, Tri; Priawandiputra, Windra (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2026)
Stingless bees of the genus Lepidotrigona are difficult to distinguish morphologically due to their similar external characteristics. This study aims to characterize the morphological, morphometric, and nest entrance structures of Lepidotrigona collected from Sibolga, North Sumatra. The methods used in this research are qualitative and quantitative. The study was conducted at the Biosystematics and Animal Ecology Laboratory, IPB University. Identification of stingless bees based on morphological and morphometric characters of the head, thorax, wings, legs, and abdomen. The nest entrance character is described of the shape, texture, and color of the nest. Results showed that the morphometric measurements of the Lepidotrigona worker bees had 5.13±0.254 mm body length, 0.80±0.223 mm mandible length, and 0.29±0.013 mm mandible width. The mesoscutum was black with short and yellow hair were observed on the edge of mesoscutellum. On the lateral side of thorax exist pale-yellow hairs. The length of fore wings from tegula was 5.39±0.125 mm, the distance between the venations (M-Cu) bifurcation and basal tip of the marginal cell was 1.55±0.023 mm, and the number of hammuli in the hind wing is six. The hind tibia was black-brownish with long hair on the edges. The length of tibia was 1.67±0.399 mm, and tibia width was 0.72±0.025 mm. The dorsal abdomen had 4-5 tergits and the first tergit was yellow with two black spots. The nest entrance of Lepidotrigona colony was characterized by round-like funnel with a diameter of 16,2 mm and a length of 102 mm. The nest entrance is funnel-shaped and light brown in color with a soft and sticky texture. Based on the morphological, morphometric and nest entrance characteristics of the genus Lepidotrigona, it is closer to species of Lepidotrigona terminata.